2015
DOI: 10.1002/rcm.7406
|View full text |Cite
|
Sign up to set email alerts
|

Diet‐tissue discrimination factors and turnover of carbon and nitrogen stable isotopes in tissues of an adult predatory coral reef fish, Plectropomus leopardus

Abstract: This study informs future interpretation of stable isotope data for medium- to large-sized fish and demonstrates that DTDFs developed for temperate fish species, particularly for δ(15)N values, may not apply to tropical species. Sampling of muscle and/or RBC is recommended for a relatively long-term representation of feeding habits, while plasma and/or fin should be used for a more recent indication of diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 105 publications
13
56
0
Order By: Relevance
“…This apparent hierarchy in the turnover rates of fish muscle, fin and scale tissue was a contrast to Matley et al (2016) who revealed in an adult coral reef fish Table 3 Best-fitting models for (1) time-based models and (2) growth-based models for 15 N turnover in muscle, fin and scale tissues of Barbus barbus, where c, turnover rate constant; m, metabolic constant; k, growth constant; Pm, relative contributions of metabolism to turnover; Pg, relative contributions of growth to turnover; Dm, relative contribution of metabolism to turnover; Dg, relative contribution of growth to turnover; T 0.5 , half-life (days); G 0.5 , half-life (g); df, estimated equilibrium value Plectropomus leopardus (Lacepède, 1802) muscle had a relatively long turnover rate compared with fin tissue. Other studies have, however, revealed that considerable differences in turnover rates can be apparent between fish tissues (Buchheister & Latour, 2010;Xia et al, 2013b), although their differences are often only minor (Hesslein et al, 1993;Sweeting et al, 2005;McIntyre & Flecker, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…This apparent hierarchy in the turnover rates of fish muscle, fin and scale tissue was a contrast to Matley et al (2016) who revealed in an adult coral reef fish Table 3 Best-fitting models for (1) time-based models and (2) growth-based models for 15 N turnover in muscle, fin and scale tissues of Barbus barbus, where c, turnover rate constant; m, metabolic constant; k, growth constant; Pm, relative contributions of metabolism to turnover; Pg, relative contributions of growth to turnover; Dm, relative contribution of metabolism to turnover; Dg, relative contribution of growth to turnover; T 0.5 , half-life (days); G 0.5 , half-life (g); df, estimated equilibrium value Plectropomus leopardus (Lacepède, 1802) muscle had a relatively long turnover rate compared with fin tissue. Other studies have, however, revealed that considerable differences in turnover rates can be apparent between fish tissues (Buchheister & Latour, 2010;Xia et al, 2013b), although their differences are often only minor (Hesslein et al, 1993;Sweeting et al, 2005;McIntyre & Flecker, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Lethal sampling is, however, not desirable, particularly when studying highly threatened fish species or where anaesthesia may reduce the ability of the animal to recover. Several recent studies have used non‐lethal sampling approaches, including the sampling of mucus, scales, blood, and fin, as alternatives to white muscle. For most fish species, fin tissue has been found to be the most isotopically similar to muscle tissue, making fins viable alternatives to muscle tissue .…”
Section: Introductionmentioning
confidence: 99%
“…; Summer Flounder Paralichthys dentatus , t 1/2 = 49–107 d: Buchhesiter and Latour ; Leopard Coralgrouper Plectropomus leopardus , t 1/2 = 83 d: Matley et al. ) that may have reflected the entire summer. However, we only considered late sources for Sheepshead liver because liver quickly turns over (e.g., Japanese Seabass, t 1/2 = 5–14 d: Suzuki et al.…”
Section: Methodsmentioning
confidence: 99%
“…; Summer Flounder, t 1/2 = 10–20 d: Buchhesiter and Latour ; Leopard Coralgrouper, t 1/2 = 10 d: Matley et al. ), and it was unlikely that sources from early summer made a substantial contribution to liver isotope composition in late summer.…”
Section: Methodsmentioning
confidence: 99%